Lifelong testicular differentiation in Pleurodeles waltl (Amphibia, Caudata) - Chesnel Amand; Chardard Dominique; Dumond Hélène; Flament Stéphane (BMC, 2009)
Abstract Background In numerous Caudata, the testis is known to differentiate new lobes at adulthood, leading to a multiple testis. The Iberian ribbed newt Pleurodeles waltl has been studied extensively as a model for sex determination and differentiation. However, the evolution of its testis after metamorphosis is poorly documented. Methods Testes were obtained from Pleurodeles waltl of different ages reared in our laboratory. Testis evolution was studied by several approaches: morphology, histology, immunohistochemistry and RT-PCR. Surgery was also employed to study testis regeneration. Results In this species, the testis is linked to the lung. This association consists of connective tissue derived from the mesorchium and the coelomic epithelium surrounding the lung and takes place at the end of larval life. This tissue contains lobules including primordial germ cells with a typical large and polylobular nucleus. The anterior part of the testis remains thin and undifferentiated while the posterior part differentiates in a large first testis lobe where spermatogenesis occurs during the first year of life. The undifferentiated status of the anterior part is attested by the lack of expression of the testis marker Dmrt1 and the meiosis entry marker Dmc1. Three-year-old Pleurodeles waltl possess multiple testes made up of two lobes. The second lobe appears at the caudal extremity of the first one from residual primordial germ cells located near or even inside efferent ducts in the glandular tissue that usually appears following spermatozoa extrusion. Surprisingly, in the case of surgical elimination of the anterior part of the testis, de novo spermatogenesis is stopped in the first lobe which becomes restricted to the glandular tissue. Following first testis lobe removal, the anterior part of the testis regenerates a new testis lobe, a process stimulated in the presence of DHT. Conclusion Pleurodeles waltl constitute an original gonochoristic vertebrate model in which testis differentiation is observed up to adulthood.